Potential of X-ray computed tomography for 3D anatomical analysis and microdensitometrical assessment in wood research with focus on wood modification. (1st August 2013) - Van den Bulcke, J; Biziks, V; Andersons, B; Mahnert, K-C; Militz, H; Van Loo, D; Dierick, M; Masschaele, B; Boone, M N; Brabant, L; De Witte, Y; Vlassenbroeck, J; et al.
Abstract : Studying structure and chemistry of wood and wood-based materials is the backbone of all wood research and many techniques are at hand to do so. A very valuable modality is X-ray computed tomography (CT), able to non-destructively probe the three-dimensional (3D) structure and composition. In this paper, we elaborate on the use of Nanowood, a flexible multi-resolution X-ray CT set-up developed at UGCT, the Ghent University Centre for X-ray Tomography. The technique has been used successfully in many different fields of wood science. It is illustrated how 3D structural and microdensitometrical data can be obtained using different scan set-ups and protocols. Its potential for the analysis of modified wood is exemplified, e.g. for the assessment of wood treated with hydrophobing agents, localisation of modification agents, pathway analysis related to functional tissues, dimensional changes due to thermal treatment, etc. Furthermore, monitoring of transient processes is a promising field of activity too.